Social bots' role in online political communication: Evidence from German Federal Election 2021 - Abeer Ibtisam Aziz (Philipps-University Marburg, School of Business and Economics, 2023)
In 2016, the US elections and Brexit changed the perception and understanding of how social media platforms could influence political outcomes. This has been complemented by the advancement in automation and data processing. This paper studies the influence of bots on online information diffusion and political discourse around the 2021 German Federal Elections. It examines the behavior of social bots in online political communication, in particular, whether the presence of bots leads to an amplification of the Tweet volume of humans. Using Twitter data pertaining to the German political sphere over 6 weeks till election day, I find 6% of the tweets originated from bot accounts. The impact of the bots is investigated through time series analysis. The key findings are that the bots' tweet volume significantly impacts the human tweet volume, especially when the tweets hold the same inclination towards a political party. The influence is not always observed for across-inclination tweet volumes of bots on humans. Furthermore, employing impulse response functions, the impact is observed to be positive, indicating an amplification effect of bots' tweeting activity.
Keywords: D72; D83; D84; C32; 330; Political communication; social bots; Germany; Twitter